Proceedings of the Ocean Drilling Program 1989
DOI: 10.2973/odp.proc.sr.104.191.1989
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Vøring Volcanic Margin

Abstract: ODP Sites 642 and 643 recovered a succession of rocks which have greatly improved the understanding of how the Cenozoic volcanic Wring Margin evolved, particularly by providing important constraints on the series of events that occurred during the initial opening of the Norwegian-Greenland Sea. The more than 900 m of igneous rocks and interbedded sediments drilled at Site 642 constitute two distinct, strikingly different volcanic series. The upper series, composed of transitional mid-oceanic tholeiitic lava fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
115
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 100 publications
(223 reference statements)
3
115
0
Order By: Relevance
“…Thick igneous layers were also intruded as sills into the continental crust or extruded sub-aerially as flood basalts. This magmatism decreased significantly after 5e10 myrs of oceanic spreading (Eldholm et al, 1989;White and McKenzie, 1989;Mjelde et al, 2008a).…”
Section: Tectonic Settingmentioning
confidence: 93%
“…Thick igneous layers were also intruded as sills into the continental crust or extruded sub-aerially as flood basalts. This magmatism decreased significantly after 5e10 myrs of oceanic spreading (Eldholm et al, 1989;White and McKenzie, 1989;Mjelde et al, 2008a).…”
Section: Tectonic Settingmentioning
confidence: 93%
“…Here coring demonstrated that the shallower layers are lava flows and volcaniclastic layers (Planke et al, 2000). These margins have generally complex structures owing to changes in tectonic setting across the margin as well as the combination of subaerial, submarine, and shallow-water explosive volcanic products (Eldholm et al, 1989;Larsen et al, 1994). The closest analog to oceanic plateau volcanism occurs in the outer "seaward dipping reflector" (SDR) complexes, which are interpreted as stacks of submarine sheet flows erupted into deep water (Planke et al, 2000).…”
mentioning
confidence: 89%
“…Among these are: Initiation of seafloor spreading in the Eurasia Basin (Jackson and Gunnarson, 1990;Kristoffersen, 1990), separation of Greenland from Eurasia during chron 24R (e.g. Eldholm et al, 1989), and final separation of Greenland from North America in the Paleocene (Chalmers et al, 1993). Unconformity LS2 marks the top of a highly reflective sequence which is absent on the most elevated horsts.…”
Section: Laptev Sea Shelfmentioning
confidence: 99%